An epidemic and economic growth. A medium-term perspective - Bolińska, Monika; Dykas, Paweł; Tokarski, Tomasz; Wisła, Rafał (Publishing House of Wroclaw University of Economics and Business, 2024)
The described model of economic growth under conditions of an epidemic does not directly refer to the social and economic situation in the years 2020 and 2021, i.e. to the COVID-19 pandemic. It is aimed to identify the consequences of any epidemic leading to severe social losses (high percentages of the infected and dead, limited interpersonal contacts as a result of lockdown, a lowered level of general individual and social well-being) and economic losses (a fall in production as a result of the collapse of aggregate demand and a reduction in the supply capacity of the economy, and consequently a decreased rate of capital accumulation). The described epidemiological-economic model combines the SIR epidemiological model from 1927 (with its modification proposed in 2020 by Bärwolff) and the neoclassical growth model proposed by Solow in 1956. The authors expanded the concept by lockdown restrictions with various levels of their severity, considering specific rules for their implementation, and by guidelines for scenario analyses of changes in the value of social and economic activity index, in the value of aggregate production, in the capital stock accumulated in the economy and in social utility. The effect of an epidemic on medium-term economic growth was also considered, for various levels of economic development (measured by the distance of input capital stock from that formed in a long-term equilibrium in the Solow model). The principal conclusions drawn from the discussion are listed below. First, the introduction of the same restrictions imposed on social and economic activity throughout the territory of a country poses a considerable risk of error in assuming a uniform spread of the epidemic. Second, a rapid introduction of lockdown measures has a stronger effect on accumulated social and economic activity than a continual process of gradual imposing and lifting restrictions on that activity. Third, a scenario of a rapidly imposed severe lockdown has the most drastic consequences for the economy, causing both the sharpest drop in production, the longest time of remaining on the path of relatively lowest growth, and the most dramatic expected accumulated decrease in production. Similar conclusions are drawn as to the changes in social utility.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 18-36
Keywords: SIR model; Solow model; epidemic; lockdown; social utility